A new Culeolus species (Ascidiacea) from the NE Pacific, California - Sanamyan, Karen; Sanamyan, Nadya; Kuhnz, Linda (Zootaxa, 2018)
The paper describes Culeolus barryi n. sp. (Ascidiacea: Pyuridae), a species photographically documented in situ and collected in the northeast Pacific, off the coast of California (USA). This species of stalked tunicate inhabits deepwater (1200 m) and is characterized by numerous gonads on each side of the body. It is most similar to C. nadejdae from the Sea of Okhotsk and C. sluiteri from Aleutian Islands. A brief overview of all Culeolus species is provided.